On the central power of the Dirichlet series - Dagienė, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. Дагене. О центральном показателе ряда ДирихлеE. Dagienė. Apie Dirichle eilutės centrinį rodiklį